The role of green roofs in post COVID-19 confinement: An analysis of willingness to pay. (December 2021) - Manso, Maria; Sousa, Vitor; Silva, Cristina Matos; Cruz, Carlos Oliveira
Abstract: Urban population is becoming less likely to contact with nature. Yet, green infrastructure, as green roofs, provide multiple ecosystem services, as promoting citizens physical and psychological well-being. With the Coronavirus 19 world pandemic public spaces, like parks and other recreational areas, were closed and most citizens were confined to their dwellings. In this context, the need for outdoor space in the housing environment became more necessary than ever. This study is based on a survey performed to citizens living in 35 different countries to identify their access and value given to existing green areas in the home environment during and after confinement, and their willingness to pay (WTP) for an accessible green roof. Results indicate that 68% of respondents missed having a garden during the confinement and the outdoor space value increased after the confinement. Most are willing to pay for a medium sized accessible green roof and their WTP increases if the green area is bigger. WTP for medium sized green roofs is higher in other countries than in Portugal but not significantly different for larger green roofs. To promote private investment in green roofs, citizens WTP should be considered when designing new urban green infrastructure incentive policies. Highlights: The COVID-19 had impact on the access to urban green spaces. Survey performed to citizens who were in confinement conditions. Analysis the access and value given to existing green areas at home. Perception of green spaces in the home environment has changed. Most citizens are WTP for an accessible green roof in their home.